(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article discusses the results of the study of the sampling process, depending on the working bodies of the feeding zones of the pneumatic spinning machines. The results of the experiment of the feeding zones of rotor spinning machines, depending on their main working bodies, are presented. Optimal parameters of the needle sampling drum angle for gaining high quality yarn from the slope angle of the front part of the sampling drum from the reduced elastic coefficient of the steel stator base and coefficients of breaking for the breaking load at the angle of inclination of the bottom part of the sampling drum from the reduced elastic coefficient of the warp base are given.